Rapid Antimicrobial Susceptibility Testing Methods for Blood Cultures and Their Clinical Impact - Banerjee, Ritu; Humphries, Romney (Frontiers in Medicine, 2021)
Antimicrobial susceptibility testing (AST) of bacteria isolated in blood cultures is critical for optimal management of patients with sepsis. This review describes new and emerging phenotypic and genotypic AST methods and summarizes the evidence that implementation of these methods can impact clinical outcomes of patients with bloodstream infections.